Crisis and the emergence of illicit markets: A pragmatist view on economic action outside the law - Matías Dewey (Max Planck Institute for the Study of Societies, 2014)
Although illicit exchange has also been an organized, silent, and ever-present response to harsh economic crisis, only protest and social movements have captured scholars' attention. In order to fill this void, this paper analyzes the emergence of illegal markets under situations of social breakdown. I claim that an illicit market emerging under socio-economic crisis conditions might be understood as the result of a constant valuation process and the intervention of what Herbert Mead called generalized others. In the new arena of exchange, individuals are able to anticipate the reactions of others, inhibit undesirable impulses, and guide their conduct accordingly by visualizing their own line of action from a generalized standpoint. This approach to illicit markets is based on a critical reading of two other approaches: the anomie theory and the field of organized-crime studies. Both perspectives, according to the argument, operate with a model of action characterized by fixed ends and means, a priori assumptions that hinder the ability to perceive the gradual and transforming dynamics of a crisis situation. The paper also offers empirical evidence on the process of the emergence of an illicit market under a crisis situation. By referring to La Salada market, an arena of exchange which emerged during the 1990s in Argentina, I describe a process characterized by an intensification of communicative activities, the adjustment of mutual expectations, the search for definitions that legitimate expectations, and role-taking in the market. – – Illegaler Markttausch ist oft die leise, aber organisierte und stets präsente Antwort auf ökonomische Krisen. Trotzdem waren bisher nur Protest- und soziale Bewegungen als Krisenreaktionen Gegenstand soziologischer Forschung. Diese Studie soll die Lücke füllen und analysiert das Aufkommen illegaler Märkte in Zeiten sozialen Zusammenbruchs. Der Autor argumentiert, illegaler Markttausch unter den Bedingungen einer sozioökonomischen Krise könne als Ergebnis eines konstanten Bewertungsprozesses und als die Intervention der von Herbert Mead so bezeichneten generalized others verstanden werden. Die neu entstandene Marktarena versetzt Akteure in die Lage, Reaktionen anderer zu antizipieren, unerwünschte Impulse zu unterbinden und ihr Verhalten anzupassen, indem sie ihr Vorgehen von einem allgemeinen Standpunkt aus betrachten. Diese Herangehensweise an illegale Märkte beruht auf einer kritischen Lesart zweier bestehender Ansätze: der Anomietheorie und der Studien zu organisierter Kriminalität, die beide auf einem Akteurmodell mit vom Handlungsprozess losgelösten Zielen und Mitteln basieren. Solche vorweggenommenen Einschätzungen, so die Argumentation, schränken die Fähigkeit ein, graduelle und sich transformierende Dynamiken einer Krisensituation wahrzunehmen. Am Beispiel von La Salada, einer Marktarena, die während der 1990er-Jahre in Argentinien entstanden ist, beschreibt der Autor die Entstehung eines illegalen Marktes in einer Krisensituation. Er untersucht einen Prozess, der von einer Intensivierung kommunikativer Aktivitäten, von der Korrektur gegenseitiger Erwartungen und der Suche nach legitimierenden Definitionen sowie dem role-taking im Markt geprägt ist.
Keywords: 300